ADMINISTRASI NEGARA DAN OTONOMI DAERAH: KAJIAN PUSTAKA TENTANG DESENTRALISASI DAN EFEKTIVITAS PELAYANAN PUBLIK - Muhammad Bagus Adi Wicaksono (CV. Adiba Aisha Amira, 2026)
Decentralisation and regional autonomy are important parts of state administrative reform aimed at improving the effectiveness of public services and the responsiveness of government to the needs of the community. However, the implementation of decentralisation in various regions has shown mixed results and has not yet fully achieved the expected objectives. This study aims to examine the relationship between state administration, regional autonomy, and the effectiveness of public services through a qualitative approach based on literature review. The research data was obtained from reputable academic literature discussing decentralisation, governance, and public services. The analysis was conducted using thematic analysis techniques to identify the main factors that influence the effectiveness of public services at the local level. The results of the study show that the effectiveness of public services in the context of regional autonomy is greatly influenced by the institutional capacity of local governments, coordination between levels of government, and the application of good governance principles. Limited resources and weak coordination between central and regional policies are major challenges in realising effective and equitable public services. This study emphasises that strengthening state administration and governance is an important prerequisite for the success of decentralisation in improving the quality of public services at the local level.